Dipeptidyl peptidase IV (DPP-4) inhibition alleviates pulmonary arterial remodeling in experimental pulmonary hypertension. (October 2018) - Xu, Jian; Wang, Jingjing; He, Mengyu; Han, Honghao; Xie, Weiping; Wang, Hong; Kong, Hui
Abstract Dipeptidyl peptidase IV (DPP-4) is well known for its role in glucose homeostasis, and DPP-4 inhibitor (DPP-4i) exhibits multiple actions in cardiovascular diseases. However, the effect of DPP-4i on pulmonary hypertension (PH) remains unclear. Therefore, this study aims to investigate the effect of DPP-4i on pulmonary arterial remodeling in rats with PH and the potential underlying mechanisms. Our results show that DPP-4 was expressed in epithelial cells, endothelial cells, smooth muscle cells, and inflammatory cells in lung. DPP-4i (Sitagliptin) attenuated right ventricular systolic pressure (RVSP), right ventricle remodeling, hypertrophy of pulmonary arterial medial layer, inflammatory cell infiltration, and endothelial–mesenchymal transition (EndMT) in monocrotaline (MCT)-induced PH rats. Similarly, DPP-4i also alleviated bleomycin- and chronic hypoxia-induced PH in rats. In cultured human pulmonary arterial smooth muscle cells (PASMCs), DPP-4i inhibited platelet derived growth factor (PDGF)-BB-induced proliferation and migration, which was abolished by phosphatase and tensin homolog deleted on chromosome ten (PTEN) knockout. These results demonstrate that DPP-4 inhibition alleviates pulmonary arterial remodeling in experimental PH by inhibiting proliferation and migration of PASMCs. Currently, therapeutic choices for patients with pulmonary hypertension (PH) are limited. This paper reveals that dipeptidyl peptidase IV inhibition alleviates pulmonary arterial remodeling in PH by decreasing the proliferation and migration of pulmonary arterial smooth muscle cells by regulating PTEN/AKT/MAPK signaling. Therefore, soluble DPP-4 might be a diagnostic or prognostic marker for PH; and DPP-4 inhibitors, potential treatments.